The Implementation of Activity-Based Costing on Black Rice Supply Chain in Sleman District, Yogyakarta - Anggriani Dwi Putriasih; Dyah Ismoyowati; Endy Suwondo (APTA and DTIP FTP UGM, 2021)
As the primary rice consumers, Indonesians, especially people in Yogyakarta, particular consumers progressively changed their carbohydrate intake from white rice to black rice because of human health benefits. Consequently, from 2015 to 2018, Yogyakarta black rice farm extended its arable land, production, and productivity to fulfill the demand. The research aims to help the actor of business to supervise the activities, wasting higher costs and reducing the profit by analyzing the logistics cost structure along the black rice supply chain with Activity-Based Costing (ABC). The results found that the highest cost proportion of farmers (63.57%), farmer groups (69.97%), and distributors (50.47%) take place in the material handling activity. In comparison, retailers spend most of the cost on inventory activity (64.29%).